Community Participation in Ecotourism Project Development: In Wof-Washa National Priority Forest Area - Shewandagne Alemayehu (MA); Berhanu Esubalew (PhD.) (Journal of Social Responsibility, Tourism and Hospitality, 2024)
The study focused on investigations of community participation in ecotourism development in Wof-Washa National Priority Forest Areas, using a descriptive design with mixed approach through cross-sectional survey. The study utilized systematic, stratified, and purposeful sampling methods. It also used thematic analysis for qualitative data collected through interviews, and descriptive statistics for quantitative data gathered via questionnaires. Document reviews were used to triangulated this study result with previous findings. The study findings reveal that the current status of community involvement in ecotourism development lean toward degree of tokenism (moderate level), with limited roles, as Arnstein’s model, at all stages. Generally, without the participation of community, the development of ecotourism project couldn’t be possible. The researcher suggests that collaborative efforts among all relevant stakeholders are crucial to fostering community participation in the successful implementation of the ecotourism project in Wof-Washa National Priority Forest Area.